Spritual And Emotional To Enhance Employee Performance With Right Target Recruitment And Job Placement Policies - Rindi Andika; Hasrul Azwar Hasibuan; Gita Pratiwi Kaban (SEAN Institute, 2022)
This study aims to analyze the effect of spiritual intelligence and emotional intelligence on improving lecturer performance. This study used primary data using a sample of 55 Staff of Village development. With the results of research with the existence of spiritual and emotional intelligence can improve lecturer work performance with an R square result of 84%.